FLEXOR TENDON INJURIES OF HAND: EXPERIENCE AT PAKISTAN INSTITUTE OF MEDICAL SCIENCES, ISLAMABAD, PAKISTAN - Ahmad, Muhammad; Hussain, Syed Shahid; Tariq, Farhan; Rafiq, Zulqarnain; Khan, M. Ibrahim; Malik, Saleem A. (Journal of Ayub Medical College Abbottabad, 2007)
Background: Flexor tendon injury is one of the most common hand injuries. This initial treatment is of the utmost importance because it often determines the final outcome; inadequate primary treatment is likely to give poor long tem results. Various suture techniques have been devised for tendon repair but the modified Kessler’s technique is the most commonly used. This study was conducted in order to know the cause, mechanism and the effects of early controlled mobilization after flexor tendon repair and to assess the range of active motion after flexor tendon repair in hand. Methods : This study was conducted at the department of Plastic Surgery, Pakistan Institute of Medical Sciences, Islamabad from 1st March 2002 to 31st August 2003. Only adult patients of either sex with an acute injury were included in whom primary or delayed primary tendon repair was undertaken. In all the patients, modified Kessler’s technique was used for the repair using non-absorbable monofilament (Prolene 4-0). The wound was closed with interrupted nonabsorbable, polyfilament (Silk 4 -0) suture. A dorsal splint extending beyond the finger tip to proximal forearm was used with wrist in 20 - 30o palmer flexion, metacarpophalangeal (MP) joint flexed at 60o. Passive movements of fingers were started from the first post operative day, and for controlled, active movements, a dynamic splint was applied. Results: During this study, 33 patients with 39 digits were studies. 94% of the patients had right dominated hand involvement. 51% had the complete flexor digitorum superficialis (FDS) and flexor digitorum profundus (FDP) injuries. Middle and ring fingers were most commonly involved. Thumb was involved in 9% of the patients. Zone III (46%) was the commonest to be involved followed by zone II (28%). Laceration with sharp object was the most frequent cause of injury. Finger tip to distal palmer crease distance (TPD) was < 2.0 cm in 71% cases (average 2.4cm) at the end of 2nd postoperative week. Total number of patients was 34 at the end of 6th week. TPD was < 2.0 cm in 55% patients and < 1.0 cm in 38% cases (average 1.5cm) at the end of 6th week. Total 9 patients were lost to the follow up at the end of 8th week. TPD was < 1.0 cm in 67% (average 0.9cm) at the end of 8th postoperative week. No case of disruption of repair was noted during the study. Conclusion: Early active mobilization programme is essential after tendon repair. Majority of the patients (92%) had fair to good results at the end of 2nd week which increased to 97% at the end of 8th week to good to excellent. Keywords: Flexor Tendon Injury, Modified Kessler’s repair, Dynamic Splint